"Well-fare" Economics of Groundwater in South Asia. (24th January 2017) - Jacoby, Hanan G.
Abstract : Groundwater exploitation has been instrumental in raising agricultural productivity and reducing rural poverty in South Asia, a region that accounts for nearly half of the global groundwater used for irrigation. Over the past three decades there has been an explosion of private investment in borewells and mechanized pumps, which has allowed access to groundwater to be widely shared. But this profusion of drilling and pumping has also led to serious groundwater depletion. This essay explores South Asia's groundwater dilemma through the lens of welfare economics, drawing on evidence from India and Pakistan gleaned from a variety of sources ranging from agricultural censuses to specialized surveys. Policies to arrest groundwater depletion are also discussed. JEL codes: